Application of Group Counseling with Self Instruction Techniques to Increase Student Self Efficacy in Facing Final Project - Vinda Chairunnisa; Achmad Juntika Nurihsan; Agus Taufik; Yusi Riska Yusniana (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
This study was conducted with the main purpose of identifying significant differences between the conditions before and after providing group guidance using self instruction techniques to students. The group guidance model with self-instruction techniques is used as the main treatment in an effort to increase students' self-confidence. This research uses a pre-experiment design with pre-test and post-test one group design. The research location was conducted at the Counseling Guidance Study Program, Faculty of Teacher Training and Education, Al-Washliyah Muslim Nusantara University Medan. The study population consisted of 15 students of the study program, with 6 students as samples taken using Purposive Sampling method. Data analysis using Wilcoxon test with 5% significance level. The analysis tool used was SPSS statistical software version 20. The results of the analysis showed a significant increase in students' self-confidence after receiving group guidance with self-instruction techniques. Based on the Wilcoxon test, there is a rejection of the null hypothesis (Ho) and acceptance of the alternative hypothesis (Ha), with a critical value of T at a significance level of 5% and a sample size of 6. The average pre-test score was 63.33, increasing to 87.00 in the post-test, with a difference of 24.13. This shows a significant increase in the self-confidence of Counseling Guidance students,Al-Washliyah Muslim Nusantara University Medan after receiving group guidance using self-instruction techniques. Keywords: Group Guidance, Self Efficacy, Self-Instruction Technique